The new science of "Fatigue Resistance" - Hutchinson, A. (Outside, 2021)
What separates the best endurance athletes from everyone else isn`t their amazing lab test data or power values—it`s how well they maintain those values after a few hours of exhausting exercise. For now, there are more questions than answers about fatigue resistance. But the author suspects we`ll see a lot more research about it in the years to come.